Application of Diversion Construction Technology in Hydraulic Engineering Construction. Issue 1 (June 2020) - Tao, Zhang
Abstract: Since the reform and opening up, China's various construction undertakings have developed rapidly, especially the water conservancy engineering undertaking. As a basic industry for national economic development, it has achieved leapfrog development. Water conservancy projects play an important role in the development of China's industry, agriculture and people's daily life, it can promote the development of production and life, and improve people's quality of life. Diversion construction technology is a widely used and important construction technology in basic water conservancy projects. It can reduce the impact of water flow during the construction process by using related technical measures, while ensuring the quality of water conservancy projects and improving the construction efficiency of the entire project. And other aspects have played an important role that cannot be replaced. This paper started with a brief description of diversion construction technology, and then studied the application of diversion construction technology in water conservancy projects.